Kajian Nilai Sosio Religius Pada Upacara Nyakap Uma Di Subak Umalas - Ni Wayan Murniti (Purwadita : Jurnal Agama dan Budaya, 2022)
The Tri Framework of Hinduism should be carried out in its entirety in terms of tattwa, morals, and ceremonies. The development of science and technology has led to a very rapid flow of globalization where it can have positive and negative impacts on various aspects of life. One of the impacts that must be considered is the negative impact that brings changes in the moral attitude of the younger generation of Hindus and attitudes to maintain the harmony of the environment around us. At the community level in Canggu Village, North Kuta District, especially the Subak Umalas commander. The uncontrolled behavior of the community has reduced the noble values of ethical teachings in Hinduism which are in the teachings of Tri Hita Karana (parhyangana, Palemahan, Pawongan). One of the changes that have occurred is the conversion of agricultural land which is being carried out and even the existence of Subak in Bali will shift.